Reading a target zone in Keynes's 'Indian currency and finance' - Gregor W. Smith (Queen's University, Department of Economics, 1994)
The gold-exchange standard in India 1893-1913 was characterized by a narrow target zone for the exchange rate, a wide annual range for the international interest-rate differential, and negative (seasonal) autocorrelation in interest rates. These properties are consistent with a standard target-zone model in which fundamentals are negatively autocorrelated on a Markov chain.
Keywords: F31; N13; N15; 330; target zone; Indian currency question; gold exchange standard